Optimal Cooperative MAC Strategies for Wireless VANETs With Multiple Roadside Units - Zhang, Zhou; Atapattu, Saman; Wang, Yizhu; Sun, Sumei; Sithamparanathan, Kandeepan (IEEE transactions on vehicular technology, 2025)
This paper presents an optimization approach for cooperative Medium Access Control (MAC) techniques in Vehicular Ad Hoc Networks (VANETs) equipped with multiple Roadside Units (RSUs) to enhance network throughput. We propose a distributed cooperative MAC scheme based on the Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) protocol. It integrates selective multi-RSUs probing and adaptive transmission, using a dual timescale channel access framework accounting for vehicle positions and channel fading. This framework divides the channel access into two phases: a large-scale phase that accounts for gradual changes in vehicle locations and a small-scale phase that adapts to rapid channel fluctuations. In each large-scale phase, we examine the MAC problem with a snapshot of vehicle locations, treating the multi-RSU VANET as a sequential planned decision process. We formulate the Multi-RSUs Probing and Cooperative Access (MRPCA) strategy, organized as a multi-stage approach with a multi-level threshold structure. We rigorously prove its optimality for maximizing average system throughput per large-scale phase using optimal sequential planned decision theory. We develop a distributed MAC algorithm with periodic location updates, adjusting thresholds based on inter-vehicle and vehicle-RSU distances in large-scale phases. In small-scale phases, multiple vehicles access channels following the MRPCA strategy with updated thresholds. Simulation results confirm the effectiveness and efficiency of our algorithm, offering insights into cooperative MAC in VANETs with multiple RSUs and practical implementation.